Efficacy of flavonoids-containing supplements on insulin resistance and associated metabolic risk factors in overweight and obese subjects: a systematic review and meta-analysis of 25 randomized controlled trials - Yao, Jia; Zhang, Yuan; Zhao, Jia; Wang, Xian-Zhe; Lin, Yu-Ping; Sun, Lu; Lu, Qi-Yun; Fan, Guan-Jie (Frontiers in Endocrinology, 2022)
Background: Obesity is becoming a global epidemic. Flavonoids, with anti-inflammatory and antioxidative functions, are proposed to treat insulin resistance (IR) in obese subjects. We aimed to evaluate the effectiveness and safety of flavonoids-containing supplements on IR and associated metabolic risk factors in overweight and obese participants. Methods: Randomized controlled trials (RCTs) involving flavonoids-containing supplements used to treat overweight and obese subjects with results of IR, other associated metabolic risk factors, and adverse effects published were retrieved from 5 electronic databases from the year of inception to January 2, 2022. Results: Twenty-five RCTs (n = 1950) were included. Pooled results demonstrated that HOMA-IR in the group receiving flavonoids-containing supplements significantly decreased versus the control group (WMD = -0.132, 95% CI: -0.236 to -0.027, p = 0.013). Subgroup analyses showed that HOMA-IR in the subgroup receiving flavonoid-containing mixtures significantly decreased (WMD = -0.25, 95% CI: -0.43 to -0.06, p = 0.008), whereas such result was not found in the singly-used flavonoids subgroup (WMD = -0.08, 95% CI: -0.20 to 0.05, p = 0.240). In addition, QUICKI in the experimental group had an increasing trend compared to that in the control group (WMD = 0.01, 95% CI: -0.00 to 0.02, p = 0.065). For secondary outcomes, FBG, FBI, TC, TG, SBP, weight, BMI, and WHR in the group receiving flavonoids-containing supplements dropped significantly compared to those in the controls. Adverse reactions did not differ between the group receiving flavonoids-containing supplements and the control group (RR = 0.97, 95% CI: 0.62 to 1.52, p = 0.905). Conclusion: This study showed that flavonoids-containing supplements may be efficacious and safe in improving IR and associated metabolic risk factors in overweight and obese participants. Nevertheless, doubt over the findings remains because limited RCTs per type of flavonoids-containing supplement were investigated, and many of the RCTs had a small sample size. Therefore, the findings must be validated in future research.